SOSIALISASI BERBASIS TEKNOLOGI DIGITAL DENGAN TEMA PERLINDUNGAN HUKUM TERHADAP KORBAN BULLYING DAN SANGSI HUKUM BAGI PELAKU BULLYING DI SEKOLAH MI NURUL FALAH 2 - Fricticarani, Ade; Ali, Mohamad; Farida, Gina; Rohenah; Surya, Jaka; Lutfiah, Jihan; Handito, Rama (UNIVERSITAS SERAMBI MEKKAH, 2024)
Digital technology-based socialization with the theme of legal protection for bullying victims and legal sanctions for bullying perpetrators in schools is an important effort to increase awareness and understanding among students, teachers, and parents. This socialization was conducted at MI Nurul Falah 2 and aims to provide education on the legal rights of bullying victims and legal consequences for bullying perpetrators. The socialization used various digital platforms such as educational videos, webinars, and social media to reach a wider audience. The results of the socialization showed an increase in participants' knowledge and awareness of the issue of bullying, legal protection, and the importance of creating a safe and violence-free school environment. Digital technology-based education has proven effective in delivering complex legal information in a way that is easily understood by all.